IDENTIFY SCIENTIFIC LITERACY FROM THE SCIENCE TEACHERS’ PERSPECTIVE (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
Scientific literacy is considered as a benchmark of high and low quality of science education in a country. This study aims to identify the scientific literacy of teachers and learning science relation to the issues from the perspective of a science teacher. This descriptive study involved 25 science teachers who are members of MGMP IPA in Bogor. The instrument used in this study consisted of scientific literacy tests and interviews. The results showed that 20% of teachers have scientific literacy ability in the low category, 65% in the moderate category and 15% in the high category. The problems of teaching science based on teacher perspective are 1. having difficulty to teach Integrated Science; 2. having limited knowledge related to learning models of Integrated Science; 3. lack of motivation in teaching integrated science consistently. The results of these studies form the basis that the professional trainings for junior high science teacher need to be conducted in a sustainable manner and related with the needs of their proficiency.